Immunohistochemistry as a fundamental tool for the differential diagnosis of polymorphous low-grade adenocarcinoma - De Vasconcellos, Luana Marotta Reis [UNESP]; Silveira, Vanessa Ávila Sarmento [UNESP]; Rosa, Luiz Eduardo Blumer [UNESP]; Cavalvante, Ana Sueli Rodrigues [UNESP]; Carvalho, Yasmin Rodarte [UNESP] (My University, 2006)
Polymorphous low-grade adenocarcinoma (PLGA) is a subtype of salivary gland carcinoma with a marked predilection for the minor salivary glands. The diagnosis of this lesion can be a challenge in incisional biopsies because of its similarity to other salivary neoplasms and the difficulty of analyzing its infiltrative nature and neurotropism. Diagnosis can be facilitated, however, by immunohistochemistry, a technique that has become a fundamental tool to the pathologist. The purpose of this study was analyze the immunohistochemical aspects of 4 cases that were examined in the São José dos Campos School of Dentistry. The patients included 4 women, ages 32 to 57 years (mean, 50 years), who reported an intraoral painless lesion, ranging in size from 1 to 3 cm (mean, 1.75 cm) with a variable evolution period. Histologically, the lesions showed similar aspects, characterized by polymorphous growth pattern, including solid, cribriform, trabecular, papillary, and single-file arrays. The tumors showed positivity to cytokeratins (Cks) 7 and 8 and vimentin, variable expression for Ck 14, and a negative reaction to Cks 13 and 19 and muscle-specific actin. PLGA is a tumor of the salivary gland that must be distinguished from other neoplasms for therapeutic and prognostic considerations, and the panel of antibodies employed in this study was effective for its diagnosis.
Keywords: Cytokeratins; Polymorphous low-grade adenocarcinoma; Salivary gland; Vimentin; actin; keratin; vimentin; adenocarcinoma; adult; case report; chemistry; differential diagnosis; enzyme immunoassay; female; human; middle aged; minor saliva gland; pathology; salivary gland tumor; Actins; Adenocarcinoma; Adult; Diagnosis, Differential; Female; Humans; Immunoenzyme Techniques; Keratins; Middle Aged; Salivary Gland Neoplasms; Salivary Glands, Minor